Análisis e implementación de la fidelización de clientes mediante la aplicación de inbound marketing y CRM del centro de entrenamiento funcional RG Fitness - Vargas Ruiz, Mariella del Rosario (2020)
This research’s suggests to demonstrate the increase in the percentage of customer satisfaction based on the use of inbound marketing techniques to draw and increase the number of customers (to draw the target audience of the business) and the use of CRM strategies. The research uses a mixed method with the completion of 47 surveys to RG Fitness clients, 152 surveys to non-clients, an interview to the business owner and surveys to specialists on the field of digital marketing and customer loyalty. The research shows that the use of both improvement proposals generates an increase in the percentage of customer satisfaction from 75% to 92%.